DIGITAL MEDIA AND CONTEMPORARY MODES OF CURRICULUM ORGANIZATION - Pereira Nicácio, Jailton; Trajano de Souza, Joseilson; Trajano de Souza, Josenete; Lisboa Galvão do Nascimento, Jonatha; Modesto Favacho, Kelsin; Helena de Paula Modesto Favacho, Lucia; Santos do Nascimento, Marielza; Campos Rodrigues, Mayara; Ricardo Pereira Accioly, Sérgio (Revista Gênero e Interdisciplinaridade, 2026)
This study aims to investigate the formative power of podcasts in the contemporary educational context, analyzing their capacity to create meaningful sound experiences that contribute to the cognitive, expressive and collaborative development of students. The research, based on bibliographical foundations, proposes a critical reflection on the ways in which sound language, when intentionally articulated with pedagogical projects, transforms the school space into a sensitive, authorial and dialogical environment. In addition to the instrumental valorization of technology, the study focuses on the aesthetic, symbolic and narrative dimensions of sound, understanding podcasts as a territory of discursive and affective experimentation. The analysis encompasses both the technical aspects of sound production and the subjective effects that listening to them provokes, situating audio as a device that expands the student’s presence in the learning process. By integrating speech, silence, rhythm and ambience, podcasts displace the centrality of the written word and inaugurate new ecologies of meaning, closer to everyday languages and youth cultural practices. The research thus proposes a broader understanding of education, capable of embracing listening as a pedagogical gesture and sound as the raw material of knowledge.